Variation in dietary intake and body fatness by socioeconomic status among women in the context of Costa Rican nutrition transitions - Bekelman, Traci A. (2019)
The Nutrition Transition model posits that vegetable oils, animal source foods (ASFs) and caloric sweeteners contribute to increases in adiposity and hence body mass index (BMI). Body Mass Index is increasing more rapidly among Latin American populations of low- versus high- socioeconomic status (SES). In Latin America, few studies have evaluated dietary intake and adiposity at the individual level or how they vary by SES. The objectives of this study among Costa Rican women are to: (1) compare indicators of adiposity and dietary intake by SES and (2) evaluate the relationship between intake of foods high in vegetable oils, ASFs or caloric sweeteners and body fatness. This cross-sectional study included 128 low-, middle- and high-SES women. Anthropometry was used to assess BMI, body composition and body fat distribution. Dietary recalls (n=379) were used to assess dietary intake. Body fat percent was greater in low- versus high-SES women (31.5±3.9 vs. 28.2±4.7%). Skinfold measurements at four sites on the upper and lower body were greater in low- versus high-SES women. BMI did not vary in low- versus high-SES women. Intake frequency of foods high in vegetable oils was greater in low- and middle- (1.8 and 1.8 times/day, respectively) versus high- (1.1 times/day) SES women. For individual foods, intake frequency varied significantly by SES for high fat condiments, fried vegetables, dairy, sweetened coffee/tea and pastries and desserts. Intake frequency of Nutrition Transition food categories was not associated with percent body fat after adjustment for energy intake. Indicators of body composition provide additional information beyond BMI that are useful in understanding SES-adiposity associations in Latin America. Approaches to understanding diet and adiposity in Latin America that focus on vegetable oils, ASFs and caloric sweeteners should consider within-country variation in the pace of the Nutrition Transition, especially when explaining variation in adiposity by SES.